Biotechnology Application in the Manufacture of Nata de Coco as Learning of Life Skills Student of Semester V Biology Education Department Pasir Pengaraian University - Filza Yulina Ade; Rindi Genesa Hatika (Universitas Sebelas Maret, 2015)
Biotechnology applications as learning life skills can be applied in practice making nata de coco. This study aims to determine mastery of Nata de Coco manufacture as learning life skills in students, especially mastery Academic life skills and Social Life skils in biotechnology practical activities. In addition to the practicum students are able to create fermentation-based food products are good quality coconut water from the material. The results obtained in this study shows that the majority of students have mastery Academic life skills are good views of the percentage performance indicators Academic life skills. As for the Social Life skils student mastery has excellent views of the overall performance indicators with a percentage of more than 80%. With these results it is concluded that students can foster interest in and to improve skills in making and creating a fermentation-based food products are good quality coconut water from the material.Keywords: Biotechnology, nata de coco,learning life skills